Loneliness Interacts With Cognition in Relation to Healthcare and Financial Decision Making Among Community-Dwelling Older Adults. (23rd June 2020) - Stewart, Christopher C; Yu, Lei; Glover, Crystal M; Mottola, Gary; Bennett, David A; Wilson, Robert S; Boyle, Patricia A
Abstract: Background and Objectives: Cognition is a known determinant of healthcare and financial decision making in old age. Social vulnerabilities also might play a role in such decisions; however, the evidence for this is less clear. Here, we examined the association of loneliness with decision making and tested the hypothesis that loneliness is associated with decision making via its interaction with global cognition. Research Design and Methods: Participants were 1, 121 nondemented older adults from the Rush Memory and Aging Project. Healthcare and financial decision making was assessed via a performance-based measure; loneliness was assessed via the De Jong Gierveld Loneliness Scale; and cognition was assessed via a 19-test neuropsychological battery. Results: In a regression model adjusted for age, sex, and education, global cognition was associated with decision making ( B = 2.43, SE = 0.14, p < .001) but loneliness was not ( B = −0.04, SE = 0.11, p = .72). However, in a model including the interaction of loneliness with global cognition, the interaction was significant ( B = 0.44, SE = 0.20, p = .03), such that the detrimental effect of loneliness on decision making was stronger when cognition was low. In secondary analyses examining the interaction of loneliness with 5 specific cognitive domains, the interaction between loneliness and working memory with decision making was significant ( B = 0.35, SE = 0.15, p = .02). Discussion and Implications: Our results suggest that loneliness compromises healthcare and financial decision making among older adults with lower global cognition and, more specifically, lower working memory.